Pengaruh Gaya Kepimpinan dan Motivasi terhadap Kinerja Karyawan - Megawati (Universitas Linggabuana PGRI Sukabumi, 2020)
This research aims to explain the influence of leadership style and motivation on employee performance at PT. Glostar Indonesia Cikembar Kab. Sukabumi. This type of research is quantitative with associative. The population is employees in the production department building C. Sampling using the slovin formula with an error rate of 10% is 92 respondents. Data collection techniques in this study were questionnaires and Multiple Linear Regression Analysis. With the help of SPSS 23 software. The results of this study indicate that employee performance is simultaneously influenced by leadership style and motivation by 0.550%, meaning that leadership style and work motivation contribute 55% and the other 45% are influenced by other variables. Partially, employee performance is significantly influenced by leadership style. While employee performance is not significantly influenced by work motivation.